Nucleação das escolas do campo: o caso do município de São Gabriel/RS - Pastório, Eduardo (2015)
The Rural Education in the Brazilian educational context lies in conceptual and pedagogical structuring process, however, before its incorporation as a public policy underwent profound changes during the 90s, from the decentralization policy of elementary school, which enabled the development of the process called "nucleation" in schools field. In this sense, this work has the general objective to understand the nucleation process of the Rural Schools in São Gabriel / RS, from its constitution as municipal policy, to its implementation in the analysis of territory, passing by the transformations in rural areas of the communities involved , analyzing spatial dynamics occurred. The survey was conducted through procedures, with the subsidy Approach Qualitative and Technical Case Study, using the methodological procedures of Field Research and Document, with the concept of place as a geographical category of analysis. For development work were carried out fieldwork in Schools poles of rural areas of San Gabriel/RS and the City Department of Education. From the results, the territorial unit under review was the development of the nucleation process (which consisted in the closure of isolated/multigrade schools, grouping them in central schools / serial) from a policy of city government, legally and financially supported by the Ministry Education, with arguments improvements in the quality of education, greater investment in infrastructure and manpower, and lower total cost effective in maintaining few schools. As a result, they were desativas 41 multigrade schools (smaller), with the creation of 5 new educational institutions, called "Schools Poles". As a result, the municipal government, through this initiative has offered a full primary education in rural communities, in serial form and increased physical structure of schools, with the addition of new classrooms, libraries and laboratories. In addition, there was the implementation of mandatory school transport (public) in the displacement of students and teachers to school in days up to 4 hours daily on the way home-school-home, on roads in different states of conservation and 16 vehicles of varying degrees of maintenance (outsourced and city hall), who travel daily on average 169.5 km each.